2021
DOI: 10.1111/crj.13371
|View full text |Cite
|
Sign up to set email alerts
|

How is the education component of pulmonary rehabilitation delivered in practice––Is it patient‐centred?

Abstract: Pulmonary rehabilitation (PR) is a crucial part of the management of respiratory disease, mostly delivered to those with COPD although this has widened in recent years to encompass bronchiectasis, interstitial lung disease (ILD) and asthma. 1,2 PR is defined as 'a comprehensive intervention based on a thorough patient assessment followed by patient-tailored therapies, which include, but are not limited to, exercise training, education and behaviour change, designed to improve the physical and psychological con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Therefore, the pulmonary rehabilitation program should be concerned with the aims of the program and concerned with education, support, and self-management according to objectives of the program for behavioral change and enhanced patient health. Patients have different learning styles and attention spans; therefore, the use of multiple modalities is preferred [18,19]. The previous study showed the effectiveness of a home-based pulmonary rehabilitation program using a booklet and manual.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the pulmonary rehabilitation program should be concerned with the aims of the program and concerned with education, support, and self-management according to objectives of the program for behavioral change and enhanced patient health. Patients have different learning styles and attention spans; therefore, the use of multiple modalities is preferred [18,19]. The previous study showed the effectiveness of a home-based pulmonary rehabilitation program using a booklet and manual.…”
Section: Discussionmentioning
confidence: 99%
“…Pulmonary rehabilitation programs should be concerned with education, support, and self-management according to the objectives of the program for behavioral changes and the enhancement of a patient's health. Patients have different learning styles and attention spans; therefore, the use of multiple modalities is preferred [18,19]. Multimedia in the form of videos, and flip charts for education and exercise on home-based pulmonary rehabilitation, for all learning preference stimulating perception, including visual, auditory, reading, and kinesthetics of patients, is feasible and accessible for elderly COPD patients with barriers to online communication.…”
Section: Introductionmentioning
confidence: 99%
“…Health education can enable patients to clarify treatment methods and precautions of the disease and improve their consciousness of respiratory rehabilitation and exercise training. It can also motivate patients to regulate medication and develop healthy living habits, thereby delaying the decline in lung function (48). Therefore, it is important to provide adequate health education for patients to improve treatment compliance, prompt patients to change unhealthy lifestyles and improve healthy daily life behaviors or activities (49).…”
Section: Pulmonary Rehabilitationmentioning
confidence: 99%